D̄N interaction in a color-confining chiral quark model - Fontoura, C. E. [UNESP]; Krein, G. [UNESP]; Vizcarra, V. E. [UNESP] (American Physical Society (APS), 2013)
We investigate the low-energy elastic D̄N interaction using a quark model that confines color and realizes dynamical chiral symmetry breaking. The model is defined by a microscopic Hamiltonian inspired in the QCD Hamiltonian in Coulomb gauge. Constituent quark masses are obtained by solving a gap equation, and baryon and meson bound-state wave functions are obtained using a variational method. We derive a low-energy meson-nucleon potential from a quark-interchange mechanism whose ingredients are the quark-quark and quark-antiquark interactions and baryon and meson wave functions, all derived from the same microscopic Hamiltonian. The model is supplemented with (σ, ρ, ω, a0) single-meson exchanges to describe the long-range part of the interaction. Cross sections and phase shifts are obtained by iterating the quark-interchange plus meson-exchange potentials in a Lippmann-Schwinger equation. Once coupling constants of long-range scalar σ and a0 meson exchanges are adjusted to describe experimental phase shifts of the K+N and K0N reactions, predictions for cross sections and s-wave phase shifts for the D̄0N and D-N reactions are obtained without introducing new parameters. © 2013 American Physical Society.